Co-targeting EGFR and Autophagy Impairs Ovarian Cancer Cell Survival during Detachment from the ECM - Yang, Zongyuan; Liu, Yi; Wei, Xiao; Zhou, Xiaoshui; Gong, Cheng; Zhang, Taoran; Jin, Ping; Xu, Sen; Ma, Ding; Gao, Qinglei (Current Cancer Drug Targets, 2015)
Ovarian cancer (OC) remains the most aggressive and lethal gynecological tumor characterized by massive intraperitoneal dissemination and malignant ascites. The carcinoma cells exfoliated from the primary tumor and were further transformed in the ascites microenvironment. During this suspension process, multi-cellular spheroids are formed and these aggregates represent an invasive and chemoresistant cellular population fundamental to metastatic dissemination. Activation of EGFR signaling is involved in increased cell metastasis and decreased apoptosis of ovarian cancer. The application of EGFR Inhibition in ovarian cancer was hampered for its limited benefit as a solitary therapy. In this work, our results primarily indicated that autophagy was induced in response to EGFR specific inhibitor AG1478 in OC cell lines generated spheres and ascites primary spheroids, characterized by the elevation of LC3-II, Beclin1 and Atg5. Blockage of autophagy with 3MA notably promoted spheroid death in suspension as well as AG1478-induced cell apoptosis, suggesting a protective autophagy contribution during tumor cells in suspension or under EGFR inhibition. Consequently, inhibiting autophagy with 3MA significantly enhanced the inhibitory effect of AG1478 on tumor cell peritoneal propagation in SKOV3 i.p. xenografts model. In addition, elevated EGFR, Beclin1, and Atg5 mRNA levels were associated with decreased ovarian cancer patient survival. Together, our findings suggested that targeting autophagy held the potential to improve EGFR inhibition benefit in the treatment of ovarian cancer cells during detachment from the extra-cellular matrix (ECM), and that this combination strategy might provide a new treatment option in controlling peritoneal metastasis of ovarian cancer.
Keywords: autophagy